Phenotypic Profile And Multi-Drug Resistance Of Biofilm Producing Staphylococcus Aureus And Escherichia Coli - Eidha Ali Bin-Hameed (Enhanced Knowledge in Sciences and Technology, 2022)
Background: Microbes attach to the surfaces and produce extracellular polymer matrix of biofilms are involved in a wide range of human infections such as urinary tract infections (UTIs) and surgical sites infections (SSIs). Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) are the most common bacteria producing biofilms causing nosocomial infections and considered to be highly antibiotics resistance and multi-resistance drugs (MDR). Objective: To detect the phenotypic prophile of biofilm formation S. aureus and E. coli and determine the susceptibility patterns of antibiotics in Mukalla city, Hadhramaut, Yemen. Material and methods: Sixty clinical isolates of S. aureus and E. coli were isolated from UTIs and SSIs samples and identified by standard bacteriological procedures, then subjected to biofilm detection by tissue culture plate (TCP) method. Disc diffusion method was used to determine the antibiotics susceptibility patterns. Findings: TCP method detected 33(55%) strong, 15(25%) moderate and 12(20%) weak/non-biofilm producers of S. aureus and E. coli. Biofilm forming S. aureus showed higher degree of resistance against the antibiotics amoxiclav 100%, ceftazidime 95.8%, cefotaxime 62.5%, cefadroxil 45.8%, ciprofloxacin 41.7% and ceftriaxone 25% with statistically significant correlation of amoxyclav and ceftazidime resistance and bacterial biofilm production (P-value <0.05). The rate of antibiotics resistance biofilm forming E. coli were 100% for amoxiclav, cefadroxil 91.7%, cefotaxime 75%, ceftazidime 70.8%, ceftriaxone 66.7%, ciprofloxacin 62.5% and co-trimoxazole 33.3% with statistically significant correlation of cefadroxil resistance and bacterial biofilm production (P-value <0.05). MDR showed in S. aureus and Esch. coli isolates for more than three antibiotics belonged to three or more different classes. Conclusion: The study revealed that S. aureus and E. coli isolated from nosocomial UTIs and SSIs have high degree of biofilm forming ability by TCP method. Antibiotics resistance and MDR was observed in S. aureus and E. coli isolates of biofilm producers than non-biofilm producers.